FATIGUE RELIABILITY BASED INSPECTION PLANNING OF JACKET OFFSHORE PLATFORM - HENDRA (NIM : 25004015); Pembimbing : Ir. Made Suarjana, Ph.D, CECEP
To ensure the structural integrity of offshore structure, it is necessary to carry out periodic underwater inspections. However these represent a significant cost to the operator. The reliability techniques presented in this thesis provide the operator with a tool for rationalizing and maximize the efficiency of underwater inspection plans, especially for jacket structure type. Offshore structures are predominantly subjected to oscillatory environmental loads and hence, fatigue characterizes the primary failure mode of their components. The failure criteria for fatigue are formulated using fracture mechanics principle, because for planning in-service inspection, the use of Palmgren-Miner rule (S-N curve), is not very appropriate. The Palmgren-Miner rule does not reflect the physical deterioration of member that cause some difficulties for updating inspection schedule. The first step in the optimized inspection planning is to identify the significant joints that need to be considered for inspection before proceeding to optimizing their inspection. The fatigue life was considered an appropriate parameter for choosing three joints which represent three types of members related to three different connection criticality, namely very serious (main leg), serious (vertical/diagonal bracing) and not serious (horizontal bracing). The spectral fatigue analysis S-N curve was used in this step, assuming there is a definable relation between wave height and stress range at the connections, and that any point the elevation of the sea above mean value is a stationary Gaussian random process. The total life of the structure was divided into a set of stationary sea states from eight direction and the spectrum for fully developed wind generated sea state described by the Pierson-Moskowitz spectrum was used. The next step is to perform a probabilistic fatigue-reliability analysis to calculate probability of failure and reliability of the critical joints during the service life of the platform. Three critical joints have been chosen namely join 403L-main leg, Join 403L-vertical/diagonal bracing and join 442-horizontal bracing. For case study the criterion used for inspection is maintaining minimum level of target reliability. When the reliability index reaches this value, an inspection is recommended. From numerical example the first inspection for joint 403L-main leg should be done in the 9th year, for joint 403L-vertical/diagonal bracing in the 12th year and for joint 442-horizontal bracing in the 18th year. Assuming that the inspection method will use MPI with mean crack length 11.1 mm for "no find" (no crack is detected), the next inspection for joint 403L-main leg should be done in the 14th, 19th, and 24th year, for joint 403L-vertical/diagonal bracing in the 18th and 24th year, and for joint 442-horizontal bracing does not need any inspection anymore. After the inspection is done, the actual performance of the critical joints is obtained, which enables us to update the confidence level of the joints. In the case of "no find", it is possible to update the reliability curve to reflect the increased confidence in the performance of these joints based on the inspection observation. From numerical example assuming "no find" (no crack is detected), the next updated inspection for joint 403L-main leg should be done only in the 18th year, for joint 403L-vertical/diagonal in the 22th year, and joint 442-horizontal bracing does not need any inspection anymore.